Guided Inquiry-Based E-Handout Development Using Seasons and Ecliptic Simulator to Improve Understanding of Seasons Concepts - Indah Dhamayanti; Ishafit Ishafit (Kasuari: Physics Education Journal (KPEJ), 2020)
This study aims to develop instructional media in the form of guided inquiry-based e-handout using seasons and ecliptic simulator which is suitable to be used to support the learning process of seventh grade SMP/MTs students. The research method uses the ADDIE model which includes five stages, namely the analysis stage (analyze), the planning stage (design), the development stage (develop), the implementation stage (implement) and the evaluation stage (evaluate). Research instruments include e-handout, pretest / post-test learning outcome, student response questionnaires, validation sheets. Through the developed e-handout, it is expected to improve mastery of the physics concept of seasons. E-handout learning has gone through the validation test stage with a score of 3.51 with a very good category so that it is declared feasible according to material experts to be used as a learning medium in the classroom. The improvement of student learning outcomes through the use of guided inquiry-based e-handout using seasons and ecliptic simulator to increase students' understanding of the concept of seasons is indicated by a standard gain value of 0.66 in the moderate category. Thus, the development of guided inquiry-based e-handouts using seasons and ecliptic simulator is suitable to be used as a science/ physics learning medium and able to improve understanding of seasons concepts.